2009
DOI: 10.1002/ejoc.200900583
|View full text |Cite
|
Sign up to set email alerts
|

Functional Chimeras: New Bingel–Hirsch‐Type Steroid–Fullerene Hybrids

Abstract: Cyclopropanations between C60 and readily available malonates bearing different steroid moieties (4–6) by the Bingel–Hirsch protocol has allowed the synthesis of a new series of hybrid functionalized chimeras (7–9). Whereas cycloadducts 7 and 8 showed the expected chemical structures, the presence of the diene moiety in the ergosterol unit of malonate 6 resulted in the production of the corresponding cycloadduct with an additional oxygen molecule. A thorough spectroscopical study (1H and 13C NMR, COSY, DEPT, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 82 publications
3
20
0
Order By: Relevance
“…[28] In this sense, the Bingel-Hirsch methodology has allowed us to obtain a variety of methanofullerenes coupled to different steroid moieties such as cholesterol, -sitosterol, and ergosterol, which are soluble in different organic solvents and potential molecular prototypes to explore the bio-medical applications of C 60 -steroids conjugates. [29] In addition, our group has also developed a synthetic strategy to prepared dumbbell-type fullerene-steroid hybrids, endowed with two [60]fullerene moieties covalently attached through the naturally occurring steroid hormone epiandrosterone. The two C 60 moieties were introduced considering a combination of Bingel-Hirsch cyclopropanation reactions and 1,3-dipolar cycloaddition processes considering steroid dimalonate units adequately functionalized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] In this sense, the Bingel-Hirsch methodology has allowed us to obtain a variety of methanofullerenes coupled to different steroid moieties such as cholesterol, -sitosterol, and ergosterol, which are soluble in different organic solvents and potential molecular prototypes to explore the bio-medical applications of C 60 -steroids conjugates. [29] In addition, our group has also developed a synthetic strategy to prepared dumbbell-type fullerene-steroid hybrids, endowed with two [60]fullerene moieties covalently attached through the naturally occurring steroid hormone epiandrosterone. The two C 60 moieties were introduced considering a combination of Bingel-Hirsch cyclopropanation reactions and 1,3-dipolar cycloaddition processes considering steroid dimalonate units adequately functionalized.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years ours research groups have collaborated in the design and preparation of C 60 ‐steroid conjugates considering several synthetic protocols . In this sense, the Bingel–Hirsch methodology has allowed us to obtain a variety of methanofullerenes coupled to different steroid moieties such as cholesterol, β‐sitosterol, and ergosterol, which are soluble in different organic solvents and potential molecular prototypes to explore the bio‐medical applications of C 60 ‐steroids conjugates . In addition, our group has also developed a synthetic strategy to prepared dumbbell‐type fullerene‐steroid hybrids, endowed with two [60]fullerene moieties covalently attached through the naturally occurring steroid hormone epiandrosterone.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, steroids are ideal blocks of molecular construction widely used in the design of drugs, due to their biological activity and specific interaction with hormone receptors . It has been demonstrated that the covalent functionalization of C 60 with a steroid unit changes its physicochemical properties, in particular its solubility and biocompatibility …”
Section: Introductionmentioning
confidence: 99%
“…The covalent linkage of C 60 to moieties, such as porphyrins [3], anionic polymethine cyanine [4], and other bioactive molecules such as amino acids [5], peptides [67], nucleotides, sugars and steroids [89], have allowed the solubilization of these hybrid derivatives in aqueous media, thus enhancing certain biological activities. For the potential use of C 60 derivatives as drug delivery systems, the size of the particles is important.…”
Section: Introductionmentioning
confidence: 99%